TECHNOLOGY APPLICATION MOBILE AUGMENTED REALITY IN EDUCATION (TAMARINE): IMPLEMENTATION OF APPLICATIONS IN IMPROVING UNDERSTANDING OF MECHANICAL WAVE CONCEPTS - Nugraha, Tubagus Abdul Azis; Haryadi, Rudi; Denny, Yusrama (Jurnal Review Pendidikan dan Pengajaran, 2024)
Android based learning applications are currently developing towards augmented reality (Expanded Reality or AR) innovation. In this research, researchers chose to use teaching materials through Augmented Reality applications to increase students' understanding of concepts through the use of augmented reality (AR) applications as teaching materials. Through an innovative work model utilizing the ADDIE model. Questionnaires were used for data collection. The population in this study were class XI students of SMA Negeri 3 Pandeglang, a sample of 30 students was taken. The assessment uses the Likert model for data analysis. The results of the media expert's judgment show that the TAMARinE application obtained an average score of 4.45 with a level of 89%, so it is included in the Very Eligible classification according to competency standards and the material expert's judgment obtained an average score of 3.71 with a level of 74%, which is included in the classification. Very suitable for competency standards or suitable for use. From the results of the initial and final trials given to students, the average pretest score was 59.3 and the posttest average score was 80.6. The increase in students' understanding of the learning media developed can be seen from the difference in pretest and posttest scores. The consequence of the sum test is 0.486 with the medium class indicating that the TAMARinE application is suitable for use.